2023
DOI: 10.1039/d3sc00251a
|View full text |Cite
|
Sign up to set email alerts
|

An iodide-containing covalent organic framework for enhanced radiotherapy

Abstract: Metal-free radiosensitizers, particularly iodine, have shown promise in enhancing radiotherapy due to their suitable X-ray absorption capacities and negligible biotoxicities. However, conventional iodine compounds have very short circulating half-lives and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 96 publications
(116 reference statements)
1
14
0
Order By: Relevance
“…The high iodine content of TADI-COF ensured that this nanomaterial was an effective X-ray absorber, as substantiated by CT images and the corresponding 3D-reconstructed images of phosphate-buffered saline (PBS) dispersions of the nanostructures (Figure K). Quantitatively, a good linear relationship existed between the CT values and TADI-COF concentrations, with a specific CT value of 7.89 ± 0.06 HU/mM (I equiv), which was comparable to that of the previously reported iodide-containing cationic TDI-COF (7.69 HU/mM), yet higher than those of the two common clinical CT contrast agents, iopromide (5.97 HU/mM) and iohexol (6.15 HU/mM), and a Hf-based MOF, UiO-66­(Hf) (3.75 HU/mM) . In addition, the specific CT value of TADI-COF-Fc was 7.78 ± 0.14 HU/mM (I equiv), which was almost exactly the same as that of TADI-COF .…”
Section: Results and Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The high iodine content of TADI-COF ensured that this nanomaterial was an effective X-ray absorber, as substantiated by CT images and the corresponding 3D-reconstructed images of phosphate-buffered saline (PBS) dispersions of the nanostructures (Figure K). Quantitatively, a good linear relationship existed between the CT values and TADI-COF concentrations, with a specific CT value of 7.89 ± 0.06 HU/mM (I equiv), which was comparable to that of the previously reported iodide-containing cationic TDI-COF (7.69 HU/mM), yet higher than those of the two common clinical CT contrast agents, iopromide (5.97 HU/mM) and iohexol (6.15 HU/mM), and a Hf-based MOF, UiO-66­(Hf) (3.75 HU/mM) . In addition, the specific CT value of TADI-COF-Fc was 7.78 ± 0.14 HU/mM (I equiv), which was almost exactly the same as that of TADI-COF .…”
Section: Results and Discussionsupporting
confidence: 74%
“…Quantitatively, a good linear relationship existed between the CT values and TADI-COF concentrations, with a specific CT value of 7.89 ± 0.06 HU/ mM (I equiv), which was comparable to that of the previously reported iodide-containing cationic TDI-COF (7.69 HU/ mM), yet higher than those of the two common clinical CT contrast agents, iopromide (5.97 HU/mM) and iohexol (6.15 HU/mM), and a Hf-based MOF, UiO-66(Hf) (3.75 HU/ mM). 45 In addition, the specific CT value of TADI-COF-Fc was 7.78 ± 0.14 HU/mM (I equiv), which was almost exactly the same as that of TADI-COF. This indicated that the contribution of Fe(II) to the X-ray absorptivity was essentially negligible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…COFs can precisely assemble different molecular species into two-or three-dimensional (2D or 3D) structures. 9,10 The adjustable topology structures endow COFs with special characteristics, including porous structures, abundant active sites, and excellent electronic properties, which have attracted enormous attention on photocatalysis, sensors, and energy storage. 11−13 However, COFs always exhibit limited efficiency for charge separation and photocatalytic performance due to the strong exciton binding energy.…”
mentioning
confidence: 99%